Childhood malnutrition in patients aged 0 to 9 years attending the Miraflores Health Center in Ecuador - Alarcón, Daniel J.; Briones, Daniel A.; Intriago, Isaac E.; García, Mario A.; Villavicencio, Lissette B. (Revista Gregoriana de Ciencias de la Salud, 2025)
Child malnutrition is a public health issue that affects children’s growth and development, particularly in vulnerable communities. This study aimed to analyze nutritional conditions and associated factors in children aged 0 to 9 years attending the Miraflores Health Center in Manabí, Ecuador. A cross-sectional, descriptive, and observational study was conducted from May to September 2024 with a non-probabilistic convenience sample of 52 caregivers. Data collection involved structured surveys and an interview with healthcare personnel. Findings revealed poor dietary quality among children, characterized by high intake of carbohydrates and dairy products, and low consumption of fruits and vegetables. Most caregivers also showed limited knowledge of child nutrition. These results underscore the need to strengthen educational and community-based interventions that promote healthy eating practices from early childhood.